A Qualitative Evaluation Study of The Infant and Young Child Feeding Counselling - Fitria Nurwulansari; Deni Kurniadi Sunjaya; Dida Akhmad Gurnida; Dewi Marhaeni Diah Herawati; Ieva Baniasih Akbar (Pediomaternal Nursing Journal, 2021)
Introduction: The Infant and young child feeding (IYCF) counselling program is an international strategy to improve IYCF practices in the community. This study aimed to explore the implementation of the program through the logic model approach.Methods: A qualitative method was employed for this evaluation study. Fifteen participants were selected by purposive random sampling, and data collection was conducted by in-depth interview, focus group discussion, observation, and document study. Data were processed from transcription, reduction, coding, categorizing to data interpretation and assessed by content analysis.Results: IYCF training is a cascading training and a combination of adult and fun learning that effectively produces a mixture of counsellors who can provide counselling using the counselling cards. However, the gap in the number of cadre counsellors and the target of counselling, as well as the limited time, low financial support, over workload, and inadequate supervision, resulted in poor recording and low numbers of clients who had been exposed to counselling. Nevertheless, this counselling has a positive effect on maternal knowledge and attitude. Still, the existence of traditional community practices, family and environmental factors are barriers to the implementation of proper IYCF practices.Conclusion: IYCF counselling effectively improved IYCF practices, so it has to be continued with strengthening the number of counsellors, recording and supervision activities. Changing strategy in counselling by involving other adult household members like grandmother or neighbours are explicitly targeted for more effective in improving the practices of infant and young child feeding.